Menjaga Kedaulatan Energi Dengan Reformasi Kebijakan Diversifikasi Sumber Daya Energi - Nabila, Farah (UI Scholars Hub, 2015)
Energy sovereignty in Indonesia is experiencing problems with a decrease in national energy security. This paper highlights how the Indonesian government attempted to make their way out through the establishment of the National Energy Policy Objectives contained in Government Regulation No. 79 Year 2014. That effort encountered some obstacles. Firstly, Indonesia is very dependent on energy imports to supply the energy needs of society. Secondly, non-renewable energy reserves dwindling and Indonesia is predicted to run out in a short time. Third, renewable energy in Indonesia undeveloped. Indonesia can overcome this problem by providing incentives to developers of renewable energy resources and energy to the community to conduct research and development of alternative energy. The government should encourage people to participate in energy conservation efforts through targeted socialization, to raise public awareness in the custody of the energy sovereignty of Indonesia